Political correctness — it is an ideology - L. G. Ionin (Социологический журнал, 2013)
Leonid Ionin responds to commentaries of Irina Zhezhko on his book «Political correctness: a brave new world». He insists that political correctness — this is ideology, strongly associated with the constitutive features of modern mass democracies. However, he disputes some estimates and corrects some false, in his opinion, judgments of Zhezhko about his book. In conclusion he clarifies the ideological position he holds in the discussion.